Rights of Prisoners During Incarceration. A case study of Vietnam - BUI, THI HANH (PRAWO i WIĘŹ, 2025)
Vietnam’s Decree No. 40/2019/ND-CP on the Implementation of the Law on the Execution of Criminal Sentences provides a solid legal basis to protect the fundamental rights of prisoners, regardless of life imprisonment or imprisonment for more than five years, which restricts freedom of movement and residence. These rights include the right to food, clothing, shelter, medical care, education, work, leisure and recreation, as well as provisions for women prisoners. This law maintains that prisoners are still human beings and citizens, and as such should be granted rights similar to those of free citizens, but based on their status as prisoners. However, there are serious limitations to the effective implementation of these rights that prisoners often face. Therefore, the purpose of this study is to determine the unhindered rights of prisoners during their imprisonment, to compare the current legislation and practice regarding prisoners, and moreover, to promote recommendations for amending and supplementing the 2019 law to protect the rights of prisoners during their imprisonment.